THE EFFECT OF GOOD CORPORATE GOVERNANCE AND CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE ON COMPANY VALUE: Case Studies of Manufacturing Companies Listed on the Indonesia Stock Exchange from 2021 - 2024 - Nur Rohma Puspitasari Nur Rohma Puspitasari; Ratri Paramitalaksmi (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2026)
This study aims to investigate the effect of GCG, proxied by institutional ownership and independent commissioners, as well as CSR disclosure variables based on GRI Standard 2021 on the value of manufacturing companies listed on the IDX for the period 2021-2024. It uses a quantitative approach, with secondary data from annual and sustainability reports. The sample selection was conducted using purposive sampling techniques and resulted in 30 companies out of a total of 118 manufacturing companies. Data analysis was performed using multiple linear regression with SPSS version 27. The results showed that institutional ownership did not have a significant effect on company value, while independent commissioners had a positive effect. In addition, CSR disclosure was found to have no significant effect on company value.